IMPLEMENTASI DATA MINING UNTUK MEMPREDIKSI BENCANA ALAM DI INDONESIA (STUDI KASUS: GUNUNG AKTIF) - Ratih Nurdiyani Sari; Dwi Setyasih; Octarina Budi Lestari (Jurnal Teknik dan Science, 2024)
This research build to predict one of the natural disasters in Indonesia, that is Active Volcano which could erupt at any time. This natural disaster occurs quite often in Indonesia and results in losses for residents who live around active volcanoes. Based on this, the researcher wants to create a decision tree that can help predict the situation before a volcano erupts, which can later be applied so that residents around active volcanoes and ordinary people can know the signs before a volcanic eruption occurs. This research will use the application of data mining with the c4.5 algorithm method as a tool in creating decision trees.